THE IMPLEMENTATION OF DIFERENTIATED INSTRUCTION IN ELEMENTARY SCHOOL LEARNING - Ramadhani Alia Putri (CV Grasta Glory, 2026)
Differentiated Instruction is a learning strategy used to accommodate the diversity of students’ abilities, interests, and learning styles in elementary schools. In the learning process, students have different characteristics, so uniform learning often fails to meet the learning needs of every student. Therefore, a learning approach that can adjust the learning process to students’ conditions and potentials is needed. Through differentiated instruction, teachers can modify learning components such as content, process, product, and learning environment according to students’ needs. The implementation of this approach allows students to gain more meaningful learning experiences, increase learning motivation, and encourage active participation in the learning process. Thus, differentiated instruction becomes an important effort in creating effective, inclusive, and student-centered learning in elementary schools.